COMPARATIVE BLADES NUMBER HORIZONTAL AXIS WIND TURBINES IN PROFILE NACA 0012 USING CFD SIMULATION - Sari, Dewi Puspita; Setyanto, Djoko; Simanjuntak, Rexon Harris; Barzah, Ahmad Alfarizi; Wadirin, Wadirin; Setiyo, Edi; Hermawan, Rudi (Indonesian Journal of Engineering and Science, 2025)
This study explores the effect of blade count on the performance of low-scale horizontal axis wind turbines (HAWT) with NACA 0012 profiles using Computational Fluid Dynamics (CFD) methods. The results show that the turbine with three blades achieves the highest efficiency, with a power coefficient (Cp) of 0.54 at a Tip-Speed Ratio (TSR) of 7, while the four-blade turbine reaches a Cp of 0.48 at a TSR of 6. The mechanical power produced by the three-blade turbine is 1,040.81 W, 28% higher than that of the four-blade turbine (927.28 W). The progressive distribution of the pitch angle in the three-blade turbine minimizes the risk of stall and flow separation. These findings suggest that fewer blades can reduce flow interference and vortex-induced losses, making it an efficient solution for the wind energy potential in Indonesia. Future research should explore geometric and material variations for further optimization.